2011
DOI: 10.1089/vim.2010.0118
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Mouse Airway Epithelial Cells and Alveolar Macrophages to Virulent and Avirulent Strains of Influenza A Virus

Abstract: Influenza A virus (IAV) infection is associated with outcomes ranging from subclinical infection to severe pneumonia. In this study, we compared IAV strains BJx109 (H3N2), HKx31 (H3N2), and PR8 (H1N1), for their ability to elicit innate immune responses from mouse airway cells in vitro and their virulence in mice. The viruses differed markedly in their ability to induce disease in mice (PR8 > HKx31 > BJx109). In particular, PR8 infection was associated with high levels of virus replication and pulmonary inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 62 publications
4
93
2
Order By: Relevance
“…When the virus was inactivated by UV irradiation, PR8-induced cytokine expression in human AMs was shown to be replication-dependent [29]. Consistent with other studies on PR8 [11,27,28,32], this study reported very little, if any, productive release of PR8 into macrophage culture supernatants, even in the absence of UV inactivation. However, virus antigen in cells infected with live virus increased over the first 48 h post-infection, a response that was abrogated by UV inactivation of the virus.…”
Section: Iav Replication and Hypercytokinemiasupporting
confidence: 89%
See 3 more Smart Citations
“…When the virus was inactivated by UV irradiation, PR8-induced cytokine expression in human AMs was shown to be replication-dependent [29]. Consistent with other studies on PR8 [11,27,28,32], this study reported very little, if any, productive release of PR8 into macrophage culture supernatants, even in the absence of UV inactivation. However, virus antigen in cells infected with live virus increased over the first 48 h post-infection, a response that was abrogated by UV inactivation of the virus.…”
Section: Iav Replication and Hypercytokinemiasupporting
confidence: 89%
“…In this case, virus nucleoprotein (NP) accumulated in 20 % of infected cells, but virus release was undetected [26]. Other studies support the findings of early experiments [11,[27][28][29]. However, certain seasonal H1N1 and H3N2 strains are capable of limited productive replication in mouse bone marrow-derived macrophages (BMDMs) or human MDMs, respectively [30][31][32][33].…”
Section: Replication Of Iav In Macrophagesmentioning
confidence: 55%
See 2 more Smart Citations
“…It is notable, however, that the apparently more permissive state of alternatively activated macrophages did not lead to production of higher levels of infectious virus than are found in classically activated cells. Although there is evidence for productive influenza virus infections in human macrophages (Hoeve et al, 2012;Perrone et al, 2008;van Riel et al, 2011;Yu et al, 2011), a number of publications have reported that influenza virus infection is abortive in murine macrophages (Rodgers & Mims, 1981;Tate et al, 2010Tate et al, , 2011. Our data show that whilst there is some replication of A/WSN/33 in murine BMDMs, the ability to produce infectious virus is not related to the activation state of the macrophage.…”
Section: Discussioncontrasting
confidence: 48%